A durability performance–index for concrete: developments in a novel test method. (1st January 2015) - McCarter, W. John; Chrisp, T. Malcolm; Starrs, Gerry; Basheer, P.A. Muhammed; Nanukuttan, Sreejith; Srinivasan, Sudarshan; Magee, Bryan J.
Implementation of both design for durability and performance–based standards and specifications are limited by the lack of rapid, simple, science–based test methods for characterising the transport properties and deterioration resistance of concrete. This paper presents developments in the application of electrical property measurements as a testing methodology to evaluate the relative performance of a range of concrete mixes. The technique lends itself to in–situ monitoring thereby allowing measurements to be obtained on the as–placed concrete. Conductivity measurements are presented for concretes with and without supplementary cementitious materials (SCMs) from demoulding up to 350 days. It is shown that electrical conductivity measurements display a continual decrease over the entire test period and attributed to pore structure refinement due to hydration and pozzolanic reaction. The term formation factor is introduced to rank concrete performance in terms of is resistance to chloride penetration.